Using an rtificial neural network approach for supplier evaluation process and a sectoral application - YAYLA, AYŞE; HARTOMACIOĞLU, SELİM (My University, 2011)
In this study, a-three layered feed-forward backpropagation Artificial Neural Network (ANN) model is developed for the supplier firms in ceramic sector on the bases of user effectiveness for using concurrent engineering method. The developed model is also questioned for its usability in the supplier evaluation process. The network\"s independent variables of the developed model are considered as input variables of the network and dependent variables are used as output variables. The values of these variables are determined with factor analysis. For obtaining the date set to be used in the analysis, a questionnaire form with 34 questions explaining the network\"s input and output variables are prepared and sent out to 52 firms active in related sector. For obtaining more accurate results from the network, the questions having factor load below 0,6 are eliminated from the analysis. With the elimination of the questions from the analysis, the answers given for 22 questions explaining 8 input variables are used for the evaluation the network\"s inputs, the answers given for 3 questions explaining output variables are used for the evaluation the network\"s outputs. The data set of the network\"s are divided into four equal groups with k-fold method in order to get four different alternative network structures. As a conclusion, the forecasted firm scores giving the minimum error from the network test simulation and real firm scores are found to be very close to each other, thus, it is concluded that the developed artificial neural network model can be used effectively in the supplier evaluation process.
Keywords: Harita Mühendisliği-Geomatik; Mühendislik ve Teknoloji; Geotechnical Engineering; Engineering and Technology; MÜHENDİSLİK, ÇOK DİSİPLİNLİ; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENGINEERING, MULTIDISCIPLINARY; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Medya Teknolojisi; Mühendislik (çeşitli); Fizik Bilimleri; General Engineering; Media Technology; Engineering (miscellaneous); Physical Sciences; Supplier evaluation; Concurrent engineering; Artificial neural network